[Rocky Shore and Cliff on a Westman Island] - Streng, Evelyn Fiedler (1975)
Photograph of rocky shore and cliffside along a Westman Island. The grey cliff is covered in white dots and green foliage along the turquoise water at the bottom of the photograph. The shore to the right is covered in a vibrant green plant life. The top right corner of the photograph is obscured by a dark object.